2004
DOI: 10.1128/jvi.78.24.13901-13910.2004
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Costs Limit Viral Escape from Cytotoxic T Lymphocytes at a Structurally Constrained Epitope

Abstract: The intense selection pressure exerted by virus-specific cytotoxic T lymphocytes (CTL) on replicating human immunodeficiency virus and simian immunodeficiency virus results in the accumulation of CTL epitope mutations. It has been assumed that fitness costs can limit the evolution of CTL epitope mutations. However, only a limited number of studies have carefully examined this possibility. To explore the fitness costs associated with viral escape from p11C, C-M-specific CTL, we constructed a panel of viruses en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(95 citation statements)
references
References 55 publications
3
92
0
Order By: Relevance
“…The immunodominant Mamu-A*01-restricted CM9 epitope is highly conserved amongst SIV strains and other lentiviruses, including SIV/DeltaB670 as we now show, and virus escape within the epitope is generally uncommon and slow to evolve in infected macaques (Barouch et al, 2002Friedrich et al, 2004a;Peyerl et al, 2003Peyerl et al, , 2004. Virus escape from T-cell recognition in monkeys infected with SIVmac239 or SHIV-89.6P is associated with flanking mutations that are necessary to maintain in vitro replicative fitness (Friedrich et al, 2004a;Peyerl et al, 2003Peyerl et al, , 2004, although mutated viruses are stable and do not revert to wild-type sequence upon subsequent infection (Friedrich et al, 2004b). While only a small number of Mamu-A*01-expressing animals were followed, our findings are notable in that virus escape from this immunodominant epitope occurred relatively early in the course of infection with SIV/DeltaB670 without any consistent temporal association with flanking mutations.…”
Section: Discussionmentioning
confidence: 99%
“…The immunodominant Mamu-A*01-restricted CM9 epitope is highly conserved amongst SIV strains and other lentiviruses, including SIV/DeltaB670 as we now show, and virus escape within the epitope is generally uncommon and slow to evolve in infected macaques (Barouch et al, 2002Friedrich et al, 2004a;Peyerl et al, 2003Peyerl et al, , 2004. Virus escape from T-cell recognition in monkeys infected with SIVmac239 or SHIV-89.6P is associated with flanking mutations that are necessary to maintain in vitro replicative fitness (Friedrich et al, 2004a;Peyerl et al, 2003Peyerl et al, , 2004, although mutated viruses are stable and do not revert to wild-type sequence upon subsequent infection (Friedrich et al, 2004b). While only a small number of Mamu-A*01-expressing animals were followed, our findings are notable in that virus escape from this immunodominant epitope occurred relatively early in the course of infection with SIV/DeltaB670 without any consistent temporal association with flanking mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Such differences in sequence evolution may be due to variation in CTL efficacy or may reflect deleterious effects of particular escape mutations on the virus. Recent reports for HIV-1 and SIV illustrate that CTL escape mutations can impact viral replication (30,46,55,56), revert upon transmission to a new host (5,17,29,44,45), or require the development of numerous compensatory mutations (30,41,44,55,56). Each of these observations implies a negative impact of immune escape on the replicative capacity of the virus.…”
Section: Cd8mentioning
confidence: 99%
“…The hypothesis that CTL escape mutants have reduced fitness is supported by studies of simian immunodeficiency virus in which cloned CTL escape mutants obtained from a macaque showed slowed growth in cell culture and reversion to the CTL-susceptible wild-type sequence after inoculation into macaques lacking the major histocompatibility class I determinants necessary for the recognition of the mutant epitopes (62). Studies of escape mutants in the Gag p24 protein demonstrated that these mutations do confer substantial reductions in replication fitness, as measured in a multiplecycle cell culture assay (117,134). It is interesting that these escape mutants, when they occur, are seen primarily in patients with HLA types that are associated with the successful control of HIV viremia.…”
Section: Outcomes In Primary Hiv-1 Infectionmentioning
confidence: 78%